2009
DOI: 10.1093/hmg/ddp425
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between environmental and genetic factors modulates schizophrenic endophenotypes in the Snap-25 mouse mutant blind-drunk

Abstract: To understand the pathophysiology of neuropsychiatric disorders such as schizophrenia requires consideration of multiple genetic and non-genetic factors. However, very little is known about the consequences of combining models of synaptic dysfunction with controlled environmental manipulations. Therefore, to generate new insights into gene–environment interactions and complex behaviour, we examined the influence of variable prenatal stress (PNS) on two mouse lines with mutations in synaptosomal-associated prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 102 publications
(122 reference statements)
3
60
0
Order By: Relevance
“…This change in amino-acid sequence in SNAP-25 results in a greater affinity for the partner SNARE protein syntaxin, greater stability of the SNARE complex, and decreased exocytosis in glutamatergic terminals (Jeans et al, 2007). Interestingly, in the blind-drunk mouse, PPI abnormalities in adulthood are further enhanced if the mice are exposed to prenatal stress (Oliver and Davies, 2009). Treatment of blind-drunk mice with clozapine restored PPI to near normal levels; haloperidol was also moderately effective (Oliver and Davies, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This change in amino-acid sequence in SNAP-25 results in a greater affinity for the partner SNARE protein syntaxin, greater stability of the SNARE complex, and decreased exocytosis in glutamatergic terminals (Jeans et al, 2007). Interestingly, in the blind-drunk mouse, PPI abnormalities in adulthood are further enhanced if the mice are exposed to prenatal stress (Oliver and Davies, 2009). Treatment of blind-drunk mice with clozapine restored PPI to near normal levels; haloperidol was also moderately effective (Oliver and Davies, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in the blind-drunk mouse, PPI abnormalities in adulthood are further enhanced if the mice are exposed to prenatal stress (Oliver and Davies, 2009). Treatment of blind-drunk mice with clozapine restored PPI to near normal levels; haloperidol was also moderately effective (Oliver and Davies, 2009). Interestingly, earlier studies of rat brain slice preparations found that administration of dopamine increased SNARE complex formation, an effect that could be blocked by haloperidol (Fisher and Braun, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Further studies are necessary to investigate the role of SNAP-25 in ADHD, but with regard to animal models it would be preferable to have a model of selective SNAP-25 deficiency such as SNAP-25 heterozygous mice. It should be noted, however, that recent study involving SNAP-25 heterozygous mice failed to detect significant hyperactivity or any other behavioral abnormalities in SNAP-25 heterozygous mice and thus the phenotype of Coloboma mice is likely caused by the deficiency in other genes disrupted in this strain (Oliver and Davies 2009). …”
Section: Other Genetic Models Of Adhdmentioning
confidence: 82%
“…As the focus of this chapter lies on the effects of stress on PPI, we will not discuss the neurochemical findings from genetic animal models of schizophrenia. Genotypes that have been found to interact with early stress to influence PPI include, nuclear receptor Nurr1 heterozygosity (i.e., 12 weeks of isolation rearing - Eells et al, 2006), Snap-25 mouse mutant blind-drunk (i.e., variable prenatal stress - Oliver & Davies, 2009), and NMDA receptor hypofunction mouse mutant (predation stress - Duncan et al, 2004). Notably, the latter study made use of predator olfactory cues (i.e., rat odor), which normalized the reduced PPI that was observed under control conditions in male mutants only.…”
Section: Multiple Stressorsmentioning
confidence: 99%